Association of pitch timing and throwing arm kinetics in high school and professional pitchers - Manzi, J. E.; Dowling, B.; Wang, Z.; Kunze, K. N.; Estrada, J.; Fu, M. C.; McElheny, K. L.; Carr, J. B.; Dines, J. S. (The American Journal of Sports Medicine, 2021)
Background: Understanding the relationship between the temporal phases of the baseball pitch and subsequent joint loading may improve our understanding of optimal pitching mechanics and contribute to injury prevention in baseball pitchers.